Supplementation of protected energy in growth performance and carcass quality in Bali Cattle (Bos javanicus d'Alton) - Leo, Teik Kee (2014)
Bali cattle (Bos javanicusd’Alton) which are reared for meat production have been considered as superior meat animals with their reasonably high dressing percentage. In this study, a 120 days feeding trial was conducted to examine the effects of calcium soap of fatty acids as protected energy supplementation on growth performance, carcass characteristics, rumen fermentation and meat fatty acid composition of Bali cattle subjected to feedlot system. Twelve male Bali cattle of 24 to 30 months old were randomly selected and assigned to 2 groups of 6 animals in each and fed with basal and protected energy supplemented diets. The basal diet consisted of 43.75% (of dry matter, DM) palm kernel cake (PKC) pellets + 56.25 % (of DM) corn stover, whiletheprotected energy supplemented diet consisted of 40.62 % (of DM) PKC pellets + 3.13 % (of DM) calcium soap of palm oil fatty acids + 56.25 % (of DM) corn stover. Theanimals subjected to protected energy supplemented diet yielded significantly (p<0.05) higher final weight (343.17 ± 24.95 kg), empty live weight (323.83 ± 24.57 kg), hot carcass weight (192.16 ± 17.43 kg) and dressing percentage (59.02 ± 1.08 %) than those subjected tothebasal diet. There were no significant differences (p>0.05) in carcass length, carcass circumference and carcass compactness measured between the dietarygroups. In addition, carcass composition, rumen fermentation and fatty acid composition of skeletal muscles (supraspinatus, longissimus dorsiand semimembranosus)did not differ(p>0.05)between the two dietarygroups. In conclusion, the inclusion of calcium soap of palm oil fatty acids as protected energy supplement in thefinishing diet had improvedgrowth performance and carcass quality of Bali cattle without affecting the rumen fermentation and fatty acid composition of skeletal muscles when subjected to feedlot system.